Antioxidant and Anti-Inflammatory Effects of Garlic in Ischemic Stroke: Proposal of a New Mechanism of Protection through Regulation of Neuroplasticity - Sandra Monserrat Bautista-Perez; Carlos Alfredo Silva-Islas; Oscar Uriel Sandoval-Marquez; Jesús Toledo-Toledo; José Manuel Bello-Martínez; Diana Barrera-Oviedo; Perla D. Maldonado (MDPI AG, 2023)
Stroke represents one of the main causes of death and disability in the world; despite this, pharmacological therapies against stroke remain insufficient. Ischemic stroke is the leading etiology of stroke. Different molecular mechanisms, such as excitotoxicity, oxidative stress, and inflammation, participate in cell death and tissue damage. At a preclinical level, different garlic compounds have been evaluated against these mechanisms. Additionally, there is evidence supporting the participation of garlic compounds in other mechanisms that contribute to brain tissue recovery, such as neuroplasticity. After ischemia, neuroplasticity is activated to recover cognitive and motor function. Some garlic-derived compounds and preparations have shown the ability to promote neuroplasticity under physiological conditions and, more importantly, in cerebral damage models. This work describes damage/repair mechanisms and the importance of garlic as a source of antioxidant and anti-inflammatory agents against damage. Moreover, we examine the less-explored neurotrophic properties of garlic, culminating in proposals and observations based on our review of the available information. The aim of the present study is to propose that garlic compounds and preparations could contribute to the treatment of ischemic stroke through their neurotrophic effects.